Влияние температурного режима на уреазную активность хеликобактерной инфекции = Effects of temperature on urease activity of h. Pylori infection - Avramenko, A. A.; Shuhtina, I. N.; Shuhtin, V. V.; Bobrik, L. M.; Boris, R. N.; Zukow, W. (Journal of Education, Health and Sport, 2015)
Avramenko A. A., Shuhtina I. N., Shuhtin V. V., Bobrik L. M., Boris R. N., Zukow W. Влияние температурного режима на уреазную активность хеликобактерной инфекции = Effects of temperature on urease activity of h. Pylori infection. Journal of Education, Health and Sport. 2015;5(10):318-322. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.34431 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2810%29%3A318-322 https://pbn.nauka.gov.pl/works/674157 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.09.2015. Revised 24.10.2015. Accepted: 24.10.2015. УДК 616.3+612.56:579.835.12 ВЛИЯНИЕ ТЕМПЕРАТУРНОГО РЕЖИМА НА УРЕАЗНУЮ АКТИВНОСТЬ ХЕЛИКОБАКТЕРНОЙ ИНФЕКЦИИ EFFECTS OF TEMPERATURE ON UREASE ACTIVITY OF H. PYLORI INFECTION А. А. Авраменко *, И. Н. Шухтина **, В. В. Шухтин **, Л. М. Бобрик **, Р. Н. Борис ***, W. Zukow **** A. A. Avramenko *, I. N. Shuhtina **, V. V. Shuhtin **, L. M. Bobrik**, R. N. Boris***, W. Zukow **** *Черноморский государственный университет им. П.Могилы, г. Николаев **Одесский национальный медицинский университет, г. Одесса ***Украинский НИИ медицины транспорта МЗУкраины, г. Одесса ****Uniwersytet Kazimierza Wielkiego, Bydgoszcz *Problem Laboratory for Chronic Helikobakterioza Petro Mohyla Black Sea State University, Nikolaev **Odessa National Medical University, Odessa ***Ukrainian Research Institute for Medicine of Transport ****Kazimierz Wielki University, Bydgoszcz Summary It was the comparative characteristic of urease activity of the active form of H. pylori infection using urease test at temperature + 37 ° C and + 4 ° C. It was found that the rate of urease activity at temperature + 4 ° C in 3.9 times less than at temperature + 37 ° C. Key words: Helicobacter pylori infection, temperature regime, the rate of urease activity. Резюме ВПЛИВ ТЕМПЕРАТУРНОГО РЕЖИМУ НА УРЕАЗНИЙ АКТИВНОСТІ ГЕЛІКОБАКТЕРНОЇ ІНФЕКЦІЇ. Була проведена порівняльна характеристика уреазної активності активної форми гелікобактерної інфекції за допомогою уреазного тесту при температурному режимі + 37 °С і + 4 °С. Було з'ясовано, що швидкість уреазної активності при температурному режимі + 4 °С в 3,9 рази менше, ніж при температурному режимі + 37 °С. Ключові слова: гелікобактерна інфекція, температурний режим, швидкість уреазної активності. Резюме Была проведена сравнительная характеристика уреазной активности активной формы хеликобактерной инфекции при помощи уреазного теста при температурном режиме + 37 °С и + 4 °С. Было выяснено, что скорость уреазной активности при температурном режиме + 4 °С в 3,9 раза меньше, чем при температурном режиме + 37 °С. Ключевые слова: хеликобактерная инфекция, температурный режим, скорость уреазной активности.